Effect of preterm birth on motor development, behavior, and school performance of school-age children: a systematic review - Rafaela S. Moreira; Lívia C. Magalhães; Claudia R.L. Alves (Brazilian Society of Pediatrics, 2014)
Objectives: to examine and synthesize the available knowledge in the literature about the effects of preterm birth on the development of school-age children. Sources: this was a systematic review of studies published in the past ten years indexed in MEDLINE/Pubmed, MEDLINE/BVS; LILACS/BVS; IBECS/BVS; Cochrane/BVS, CINAHL, Web of Science, Scopus, and PsycNET in three languages (Portuguese, Spanish, and English). Observational and experimental studies that assessed motor development and/or behavior and/or academic performance and whose target-population consisted of preterm children aged 8 to 10 years were included. Article quality was assessed by the Strengthening the reporting of observational studies in epidemiology (STROBE) and Physiotherapy Evidence Database (PEDro) scales; articles that did not achieve a score of 80% or more were excluded. Summary of findings: of findings the electronic search identified 3,153 articles, of which 33 were included based on the eligibility criteria. Only four studies found no effect of prematurity on the outcomes (two articles on behavior, one on motor performance and one on academic performance). Among the outcomes of interest, behavior was the most searched (20 articles, 61%), followed by academic performance (16 articles, 48%) and motor impairment (11 articles, 33%). Conclusion: premature infants are more susceptible to motor development, behavior and academic performance impairment when compared to term infants. These types of impairments, whose effects are manifested in the long term, can be prevented through early parental guidance, monitoring by specialized professionals, and interventions.